Warm mix asphalt: Paves way for energy saving - Choudhary, Rajan; Julaganti, Ashok (Recent Research in Science and Technology, 2014)
Road transport sector in India has expanded in the last sixty years after independence, both in terms of capacity and dimensions. Today, India is having thethird largest road network in the world, with over 4.236 million km of roadways spread across the country. Currently, majority of the Indian roads are paved with Hot Mix Asphalt (HMA),which consists of aggregates and bitumen mixed together at high temperature,approximately150-170°C. The production and placement of HMA pavements has evolved over the last 130 years and recognised as a high quality engineered paving material to produce good quality pavement. During all these years, the production of HMA has modernized from manual hand mixing and placement with rakes and shovels to computerized plants feeding, placement, and compaction equipment that track location and material quality.The main concern with the production of HMA is, it requires large amount of energy and also releases enormous amount of emissions into the environment. So, the road construction industry is looking for an alternate material or a technology that reduces the amount of energy required to produce the HMA, in order to combine energy savings and environmental benefits. Warm Mix Asphalt (WMA) technology is one of the solutions. WMA technologies allow producing the asphalt material at 30 to 40°C lower temperatures than conventional HMA. This paper presents a comprehensive literature review on various WMA technologies across the globe and advantages associated with WMA technologies.It also provides details of some of the attempts done with WMA technologies in India till now.